2014
DOI: 10.2134/jeq2013.06.0236
|View full text |Cite
|
Sign up to set email alerts
|

Transport ofEscherichia coli,Salmonella typhimurium, and Microspheres in Biochar-Amended Soils with Different Textures

Abstract: The incorporation of biochar into soils has been proposed as a means to sequester carbon from the atmosphere. An added environmental benefit is that biochar has been shown to increase soil retention of agrochemicals, and recent research has indicated that biochar may be effective in increasing soil retention of bacteria. In this study we investigate the transport behavior of O157:H7, serovar Typhimurium, and carboxylated polystyrene microspheres in water-saturated column experiments for two soils (fine sand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
5
27
2
Order By: Relevance
“…Biochar was mixed with acid-washed sand at concentrations of 0%, 5%, 10%, and 15% (by volume) and placed on a roller table at approximately 50 rpm and allowed to mix overnight. These concentrations are similar to those in previously published studies (Abit et al 2012(Abit et al , 2014Bolster and Abit 2012). Following mixing, sand-biochar mixtures were stored in polypropylene or glass bottles at room temperature until column and batch sorption experiments.…”
Section: Biochar and Sand Preparationsupporting
confidence: 82%
See 1 more Smart Citation
“…Biochar was mixed with acid-washed sand at concentrations of 0%, 5%, 10%, and 15% (by volume) and placed on a roller table at approximately 50 rpm and allowed to mix overnight. These concentrations are similar to those in previously published studies (Abit et al 2012(Abit et al , 2014Bolster and Abit 2012). Following mixing, sand-biochar mixtures were stored in polypropylene or glass bottles at room temperature until column and batch sorption experiments.…”
Section: Biochar and Sand Preparationsupporting
confidence: 82%
“…While several studies have investigated various materials and industrial byproducts for reducing nutrient and pesticide concentrations in tile-drainage waters (Vandermoere et al 2018), little research has focused on reducing concentrations of microorganisms in tile-drainage waters. Based on studies showing that biochar can increase bacterial retention by several orders of magnitude in sand-packed columns (Abit et al 2012(Abit et al , 2014Bolster and Abit 2012), biochar has been investigated as an amendment to reduce pathogen and indicator organisms in biofilters treating stormwater runoff (Afrooz et al 2018;Lau et al 2017;Mohanty and Boehm 2014a, b;Mohanty et al 2014). Similarly, biochar may be a suitable amendment for use in end-of-tile filter systems to remove indicator and pathogenic microorganisms in tile-drainage waters.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study, Abit et al [65] investigated the role of biochar feedstock (poultry litter and pine chips), pyrolysis temperature (350 and 700°C), application rate (1 and 2 %), and soil moisture content (50 and 100 %) on the transport of two E. coli isolates through a fine sand soil. The authors reported that both high-temperature biochars reduced E. coli transport at the 2 % application rate, with substantially greater reductions observed with the pine chip biochar.…”
Section: Biochar Impact On Pathogen Transport and Microbial Propertiesmentioning
confidence: 99%
“…Numerous researchers have found biochar effective in increasing retention of nutrients (Laird et al, 2010;Lehmann, 2007;Schnell et al, 2012;Zhai et al, 2015) and water (Beck et al, 2011;Novak et al, 2009, Ulyett et al, 2014 in soils, with water retention linked to increased pore space and surface area after biochar addition (Basso et al, 2013;Uzoma et al, 2011). Leaching of microbes such as E. coli decreased in response to biochar treatment (Abit et al, 2014;Bolster and Abit, 2012;Mohanty et al, 2014). A similar effect on heavy metals has been documented (Park et al, 2011;Zhang et al, 2013), attributed to increased soil cation exchange capacity and sorption potential.…”
mentioning
confidence: 86%
“…Previous studies indicated that biochar was added to organic amendments at rates ranging from 0.5% to 10% on a w/w basis (Abit et al, 2012(Abit et al, , 2014Beck et al, 2011;Bolster et al, 2012;Laird et al, 2010;Mohanty et al, 2014;Zhai et al, 2015). We selected the near-median biochar addition rate of 5% (w/w) for the horse manure and, in anticipation of a higher nutrient content, 8% (w/w) for the municipal biosolids.…”
Section: Amendmentsmentioning
confidence: 99%